2014
DOI: 10.7202/1025089ar
|View full text |Cite
|
Sign up to set email alerts
|

La résistance au changement de nom de marque : ses antécédents et ses conséquences sur le capital de marque

Abstract: Cet article analyse les antécédents de la résistance interne et externe au changement de nom de marque et ses conséquences sur le capital de marque. Une recherche qualitative menée auprès de 10 managers et de 40 consommateurs, suggère que, tant en interne qu’en externe, le niveau d’implication, le bénéfice perçu du changement et leur attachement à la marque substituée peuvent diminuer la résistance au changement. Divers leviers optimisant la gestion de la résistance au changement de nom de marque sont proposés… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…According to Delassus et al (2014), resistance may arise due to the absence of information on substitution and its benefits, a lack of comprehension regarding the decision's rationale, or the perception of conflicting arguments. Communication about the substitution, then, presents one of the most important factors for the substitution to be successful (Collange, 2015;Delassus & Descotes, 2018;Kannou, 2021).…”
Section: Information About the Substitutionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Delassus et al (2014), resistance may arise due to the absence of information on substitution and its benefits, a lack of comprehension regarding the decision's rationale, or the perception of conflicting arguments. Communication about the substitution, then, presents one of the most important factors for the substitution to be successful (Collange, 2015;Delassus & Descotes, 2018;Kannou, 2021).…”
Section: Information About the Substitutionmentioning
confidence: 99%
“…Studies conducted on brand name substitution have indicated that perceived benefits resulting from the change can help minimize consumer resistance, foster positive word-ofmouth (Pauwels & Mogos, 2018) about the new retailer brand, and encourage other consumers to revisit it (Delassus et al, 2014). However, it is clear that a retailer brand substitution accompanied by additional benefits is likely to promote change and create consumer trust in the brand.…”
Section: Perceived Benefitsmentioning
confidence: 99%
“…While retailer brand attachment can foster consumer commitment and loyalty, it is likely the source of resistance behavior that may arise when retailer brands are substituted. Accordingly, when a retailer brand is substituted, attachment to the old retailer brand may act as a barrier to the adoption of the new retailer brand, upsetting the special relationship that has been built with the old retailer brand (Collin-Lachaud et al, 2012; Delassus et al, 2014;Collange, 2015).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Some retailer brands effectively succeed in presenting new brand images to their customers, whereas others encounter challenges in gaining approval or acceptance from their loyal customer base during such transitions. This approach does carry some risks, though, and the company may suffer greatly as a result since it affects how loyal customers of the old retailer brand, who are presumably the most attached to it, may be the most "resistant" to change (Delassus et al, 2014;Ahmed & Ben Rached, 2024; Kannou et al, 2024). Therefore, it is necessary to investigate how consumers evaluate the substitution processes and find potential indicators of substitution success.…”
Section: Introductionmentioning
confidence: 99%